PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PERGURUAN MUHAMMADIYAH SETIABUDI PAMULANG TANGERANG SELATAN - Johana Putri Ayu; Lilis Suryani (SINERGI : Jurnal Riset Ilmiah, 2026)
The purpose of this study is to determine the influence of Work Motivation (X1) and Work Discipline (X2) on Employee Performance (Y) at Perguruan Muhammadiyah Setiabudi Pamulang Tangerang Selatan. This study uses a quantitative method with an associative approach, aimed at determining the relationship between independent and dependent variables. The sampling technique used is saturated sampling with data collection through questionnaires involving 35 respondents. The partial results show that the variable Work Motivation (X1) on Employee Performance (Y) has the regression equation Y = 22.851 + 0.373X1 with a correlation coefficient of 0.765, indicating a strong relationship with a coefficient of determination of 58.5%. The hypothesis test shows t-calculated > t-table (6.823 > 2.035), so HO1 is rejected and Ha1 is accepted, meaning there is a significant influence of Work Motivation on Employee Performance. The other partial results show that Work Discipline (X2) on Employee Performance (Y) has the regression equation Y = 9.445 + 0.757X2 with a correlation coefficient of 0.931, indicating a very strong relationship, with a coefficient of determination of 86.7%. The hypothesis test shows t-calculated > t-table (14.696 > 2.035), so HO2  is rejected and Ha2 is accepted, meaning there is a significant influence of Work Discipline on Employee Performance. Simultaneously, the variables Work Motivation (X1) and Work Discipline (X2) on Employee Performance (Y) show the regression equation Y = 8.824 + 0.141X1 + 0.607X2 with a correlation coefficient of 0.958, indicating a very strong relationship with a coefficient of determination of 91.7%, while 8.3% is influenced by other factors. The hypothesis test shows f-calculated > f-table (176.662 > 3.280), so HO3 is rejected and Ha3 is accepted, meaning there is a significant simultaneous influence of Work Motivation and Work Discipline on Employee Performance at Perguruan Muhammadiyah Setiabudi Pamulang, Tangerang Selatan.